The effect of quail egg supplements enriched with marine macroalgae Eucheuma spinosum on the physiological condition of Sprague Dawley rats during pregnancy (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: To investigate the effect of quail egg supplements enriched with marine macroalgae Eucheuma spinosum on body weight and physiological conditions of Sprague Dawley rats during pregnancy. Materials and Methods: This study used a completely randomized experimental design. The test animals were 25 pregnant white rats aged 3 months and weighed ± 200 gm. Pregnant rats were divided into five treatments and five repetitions; each repetition contained one pregnant rat. T0: control treatment; T1: treatment group consuming quail eggs from quail fed commercial feed; T2: treatment group consuming quail eggs from quail fed with 3% E. spinosum; T3: treatment group consuming quail eggs from quail fed with 4% E. spinosum; T4: treatment group consuming quail eggs from quail fed with 5% E. spinosum. The parameters measured were egg proximate, egg iron, egg cholesterol, red blood cell (RBC), hemoglobin (Hb), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular Hb (MCH), mean corpuscular Hb concentration (MCHC), white blood cell (WBC), lymphocytes (LYM), neutrophils (NEUT), RBC distribution width (RDW), platelet distribution width (PDW), mean platelet volume (MPV), cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), glucose, superoxide dismutase (SOD), and malondialdehyde (MDA). Results: The addition of E. spinosum into quail feed at concentrations of 3%, 4%, and 5% did not show statistically significant differences (p > 0.05) in the proximate levels (water, ash, fat, protein, and carbohydrates) compared to the control. However, the analysis of iron in quail eggs indicated a significant increase (p < 0.05) in comparison to the control treatment. In addition, the supplementation of E. spinosum in the quail feed resulted in significantly reduced (p < 0.05) quail egg cholesterol levels when compared to the control treatment. Furthermore, the supplementation of quail egg produced by quail fed with E. spinosum did not significantly affect the birth weight of the pups, RBC, MCV, MCH, MCHC, WBC, LYM, NEUT, RDW, PDW, MPV, MDA, and SOD when compared to the control treatment (p > 0.05). Meanwhile, the mother weight, Hb, HCT, cholesterol, HDL, LDL, and glucose levels significantly increased (p < 0.05) compared to the control. Conclusion: The administration of E. spinosum with concentrations of 3%, 4%, and 5% can increase iron levels and decrease cholesterol levels in quail eggs. The administration of quail egg supplements produced by quail-fed additional macroalgae E. spinosum can increase body weight, Hb, and HCT in pregnant rats. The addition of marine macroalgae with concentrations of 4% and 5% can decrease the levels of cholesterol, LDL, and glucose and increase serum HDL levels in pregnant rats.J. Adv. Vet. Anim. Res., 11(4): 1114–1121, December 2024http://doi.org/10.5455/javar.2024.k862